KESULITAN BELAJAR SISWA DALAM PERSAMAAN KUADRAT: TINJAUAN LITERATUR MELALUI PERSPEKTIF ANALISIS KESALAHAN - Nurohman, Angga; Muhtadi, Dedi; Sukirwan (Universitas Islam Nusantara, 2025)
Quadratic equations are one of the fundamental components of secondary-level mathematics education and serve as a gateway to more advanced topics such as algebra, functions, and calculus. Despite their curricular significance, numerous studies have documented that students consistently experience difficulties in understanding and solving quadratic equations. This study aims to identify and classify the types of students’ learning difficulties related to quadratic equations through a systematic literature review. Using an error analysis framework, this review synthesizes findings from 14 peer-reviewed journal articles published between 2015 and 2024. The inclusion criteria cover studies that specifically examine students’ errors, misconceptions, and learning obstacles at the lower and upper secondary education levels. The review reveals three main categories of student difficulties: (1) conceptual misconceptions, such as a lack of understanding of the standard form or the properties of quadratic roots; (2) procedural errors, including incorrect application of solution methods such as factoring or completing the square; and (3) technical mistakes, such as sign errors and faulty algebraic manipulations. These findings highlight the complexity of learning quadratic equations and the importance of balancing conceptual understanding with procedural fluency in mathematics instruction. The study concludes that the implementation of error-based instructional strategies and diagnostic assessments can promote deeper comprehension and assist educators in identifying specific learning barriers. Implications for curriculum design, instructional practices, and future research directions are also discussed.